Considerations on Child Protection Against Exploitation in Spain - CREÈš, Daniela Cristina (Journal of Legal Studies, 2014)
The protection of vulnerable persons, such as children, women, or the elderly, against exploitation is sought by the European Union’s, as well as by each of its member states. In this respect, as some forms of exploitation prejudice fundamental human rights, but also considering the categories of persons affected, the European Union has stepped up to protect these persons, prevent and tackle this phenomenon, especially by strengthening cooperation and coordination between police and judicial authorities of the Member States. One of the states that have adopted strong measures to tackle and prevent the exploitation of disadvantaged groups is Spain. With regard to children, the forms in which exploitation manifests itself in Spain are different; notable among them are: physical, emotional, and sexual abuse, physical neglect, child labor, being forced into begging, prenatal maltreatment. In the following, we shall analyze these measures in the light of incidental normative acts in this matter.